Analisis Data Service Desk IT Di PT. Buma Site Lati - Della Eliyana Saputri; Wawan Joko Pranoto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Field Work Practice is a mandatory assignment for undergraduate students in Informatics Engineering at the Muhammadiyah University of East Kalimantan, Samarinda, with a weight of 2 credits. The focus of this PKL is IT Requisition (ITR), a form for requests for IT equipment outside the specified list of assets and services. Analysis of ITR and BMC data at PT. BUMA Site LATI concludes that monitoring IT service desk data shows several important points, especially regarding ITR. The results of this analysis are the basis for concluding the efficiency and effectiveness of IT services, with potential recommendations for improvement. This conclusion provides a better view of understanding and improving IT service desk services at PT. BUMA Site LATI.